Comparative evaluation of water-filled and air-charged catheters in urodynamic studies for women with stress urinary incontinence - Nikita Kazakov; George Kasyan; Igor Gritskov; Roman Stroganov; Bagrat Grigoryan; Arman Sarukhanian; Dmitry Pushkar (Continence)
Objective:: This study aimed to compare pressure measurements obtained using water-filled catheters (WFC) and air-charged catheters (ACC) during comprehensive urodynamic studies (UDS) in women with stress urinary incontinence (SUI). Materials and Methods:: A prospective comparative study was conducted on 41 female patients with SUI who underwent UDS with simultaneous placement of WFC and ACC between January and May 2024. Intravesical, abdominal, and detrusor pressures were recorded at the end of the bladder filling phase and during voiding, coughing (Pc), and the Valsalva maneuver (Pv). The Shapiro–Wilk test was used to assess the normality of the data, while the Mann–Whitney U test and Student’s t-test were applied for statistical comparison between the two catheter systems. A p-value of <0.05 was considered statistically significant. Results:: No statistically significant differences were found in intravesical pressure between WFC and ACC at the end of the filling phase (p > 0.05). However, significant differences were observed in abdominal pressure (Pabd), with ACC recording higher values (p < 0.05). No significant differences were noted in maximum detrusor pressure during voiding (p > 0.05). Intravesical pressures during coughing and the Valsalva maneuver were significantly higher with ACC compared to WFC (p < 0.05). Conclusion:: This study demonstrates significant differences between water-filled and air-charged catheters in measuring Pabd, Pc, and Pv. While both systems have their merits, careful consideration is required when interpreting results obtained with ACC. Future research should explore refining standardization protocols to enhance the reliability of urodynamic assessments.